Declines of population size and breeding performance of Magellanic penguins (Spheniscus magellanicus) in Magallanes Region, Southern Chile - Godoy Reyes, Claudia (2019)
Magellanic penguins (Spheniscus magellanicus) breed along the southern coast of South America, from Islote Pájaro Niños in Chile (33°21’S) to Complejo Islote Lobos in Argentina (41°33’S). The largest colony known in Chile is located at Isla Magdalena (IM) (52°55’S), Monumento Natural Los Pinguinos, located at the Magellan Strait and the only one mainland colony is in Seno Otway (SO) (52°58’S). The colonies of this species show mixed population growth trends in different regions of its distribution and in many areas this information is missing. We present the results of our monitoring program, updating the population size for these colonies in the southern extreme of Chile and breeding performance of IM. For IM, population estimates were conducted through circular plots of 100sqm in 2011, 2014, 2017, and 2018 and for SO trough direct count in 2014. Breeding success was estimated following 74 to 207 nests during the reproductive seasons. Population size of both colonies showed a remarkable decline compared to previous reports: 85,4% for IM(2018) from 2007 and 89% for SO(2014) from 2003. Nesting density in our 30 sample plots decreased from 0,083 nest/sqm (2011) to 0,016 nest/sqm (2018). Breeding success was similar in the seasons, from 0,97 (2017) to 1,08 (2011). Depending of the year the cause of loss of chicks and eggs were predation and rain. A redistribution of this species has been reported for other latitudes and it is crucial to continue monitoring these colonies and conduct studies to increase our understanding of the drivers of these population decline.